2018
DOI: 10.1021/acs.biochem.7b00957
|View full text |Cite
|
Sign up to set email alerts
|

eIF2B Mechanisms of Action and Regulation: A Thermodynamic View

Abstract: Eukaryotic translation initiation factor 2B (eIF2B) is the guanine nucleotide exchange factor of the GTPase eIF2, which brings the initiator Met-tRNA to the ribosome in the form of the eIF2-GTP·Met-tRNA ternary complex (TC). The activity of eIF2B is inhibited by phosphorylation of its substrate eIF2 by several stress-induced kinases, which triggers the integrated stress response (ISR). The ISR plays a central role in maintaining homeostasis in the cell under various stress conditions, and its dysregulation is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 53 publications
2
35
0
Order By: Relevance
“…GDP is more tightly bound to human eIF2 than the yeast complex and was not further stabilized by eIF5 in vitro (Sokabe, Fraser, & Hershey, 2012), but the DWEAR motif is conserved (Jennings & Pavitt, 2010b), and overexpression of eIF5 in human cells activates ATF4 reporter plasmids, in a manner similar to prior findings overexpressing eIF5 in yeast cells (Asano et al, 1999;Kozel et al, 2016;Singh et al, 2006). These data and recent modeling approaches suggest that eIF2-GDP/eIF5 interactions are critical for the yeast ISR and may be relevant to mammalian translation and the ISR (Bogorad, Lin, & Marintchev, 2018;Khan, Spurgeon, & von der Haar, 2018).…”
Section: Eif5supporting
confidence: 70%
“…GDP is more tightly bound to human eIF2 than the yeast complex and was not further stabilized by eIF5 in vitro (Sokabe, Fraser, & Hershey, 2012), but the DWEAR motif is conserved (Jennings & Pavitt, 2010b), and overexpression of eIF5 in human cells activates ATF4 reporter plasmids, in a manner similar to prior findings overexpressing eIF5 in yeast cells (Asano et al, 1999;Kozel et al, 2016;Singh et al, 2006). These data and recent modeling approaches suggest that eIF2-GDP/eIF5 interactions are critical for the yeast ISR and may be relevant to mammalian translation and the ISR (Bogorad, Lin, & Marintchev, 2018;Khan, Spurgeon, & von der Haar, 2018).…”
Section: Eif5supporting
confidence: 70%
“…As mentioned, during translation initiation, eIF2 forms a ternary complex with Met-tRNA i and GTP, which binds the 40S subunit to form the 43S PIC ( Figure 2) [24]. Phosphorylation of eIF2α at Ser-51 dramatically increases the binding affinity of eIF2 for its guanine nucleotide exchange factor (GEF) known as eIF2B, resulting in sequestration that blocks eIF2-GDP to eIF2-GTP exchange activity and consequently inhibits translation [25,26]. Different stress conditions provoke eIF2α phosphorylation by any of four related protein kinases: the heme-regulated inhibitor (HRI) in red blood cells, the protein kinase RNA-activated (PKR) that responds to viral infection, the PKR-like endoplasmic reticulum (ER) kinase (PERK) that senses ER stress in the ISR/UPR pathway, and the general control non-depressible 2 kinase (GCN2) that responds to a deficit in levels of certain amino acids [27].…”
Section: Eif2/isr Regulation Of Translation Initiationmentioning
confidence: 99%
“…After GDP dissociates from eIF2γ, it is generally considered that GTP and Met-tRNAi binding enables the detachment of eIF2 from eIF2B, stimulated by another initiation factor, eIF5 (26,27). The structural alignment of eIF2γ in the productive complex and aIF2γ in the aIF2•GTP•Met-tRNAi ternary complex (aIF2-TC) structure (28) revealed that Met-tRNAi can access eIF2 in the productive complex, without clashing with most of eIF2B ( fig.…”
Section: Catalysis Of Nucleotide Exchange On Eif2mentioning
confidence: 99%